Teacher's Role in Developing Students' Characteristics in TPQ Nurul Yaqin Purwakarta, Indonesia - Siti Maesaroh; Imam Tabroni; Lala Marlina; Yeyen Akasah (PT FORMOSA CENDEKIA GLOBAL, 2022)
Education is very important in building a good civilization, one of the things that must be considered is the role of teachers in improving students' morals so that in every behavior they have good religious values. Becoming a believer, pious and having noble character, education is not just transferring knowledge, more than that, students are expected to have behaviors that are practiced in their lives. In addition, the role of parents is also very supportive because the family is the main part in shaping the behavior and manners of children. In this study, the problem found was that there were children who made mistakes but did not want to admit such as hitting their friends and learning to apologize when they made mistakes that were difficult for children to do. The role of the TPQ 1st grade teacher, Nurul Yaqin, always relates each lesson to giving advice and providing good examples to students with the aim of improving and fostering their manners and morals. The purpose of this study was to describe the teacher's role in improving the etiquette and morals of grade 1 TPQ students in order to create children with noble character for the creation of an Islamic generation, and what factors support or hinder the development of students' manners and morals. The method used in the research uses descriptive qualitative methods to describe or clearly describe the research conducted.